Astrocyte‐Encapsulated Hydrogel Microfibers Enhance Neuronal Circuit Generation. Issue 5 (20th January 2020) - Kim, Beom Jin; Choi, Ji Yu; Choi, Hyunwoo; Han, Sol; Seo, Jeongyeon; Kim, Jungnam; Joo, Sunghoon; Kim, Hyo Min; Oh, Chungik; Hong, Seungbum; Kim, Pilnam; Choi, Insung S.
Abstract: Astrocytes, the most representative glial cells in the brain, play a multitude of crucial functions for proper neuronal development and synaptic‐network formation, including neuroprotection as well as physical and chemical support. However, little attention has been paid, in the neuroregenerative medicine and related fields, to the cytoprotective incorporation of astrocytes into neuron‐culture scaffolds and full‐fledged functional utilization of encapsulated astrocytes for controlled neuronal development. In this article, a 3D neurosupportive culture system for enhanced induction of neuronal circuit generation is reported, where astrocytes are confined in hydrogel microfibers and protected from the outside. The astrocyte‐encapsulated microfibers significantly accelerate the neurite outgrowth and guide its directionality, and enhance the synaptic formation, without any physical contact with the neurons. This astrocyte‐laden system provides a pivotal culture scaffold for advanced development of cell‐based therapeutics for neural injuries, such as spinal cord injury. Abstract : A 3D neurosupportive system, for enhanced neuronal circuit generation, is developed by confining astrocytes in hydrogel microfibers. The system not only directionally guides and accelerates the neurite outgrowth, but also enhances the synaptic formation, without any physical contact between astrocytes and neurons.